Annual Plan (2008-2009) Tribal Sub Plan and Schemes of Tad Department Government of Rajasthan - Planning Commission (Planning Commission, 2008)
Article 46 of the constitution of India has entrusted the government the responsibility of promoting the economic and educational interests of the scheduled castes and scheduled tribes. Efforts were made to fulfill this constitutional obligation in five year plans, but a new strategy for development of tribal area was evolved during Fifth Five year plan, which is continuing. The basic strategy of tribal sub-plan area development is to eliminate exploitation of the tribals by money lenders, middlemen, prosperous and affluent farmers. In devising economic programmes the socio-cultural factors have been accounted for.
Government of Rajasthan, Tribal Area Development Department